On the secrecy capacity of arbitrary wiretap channels - Bloch, M.; Laneman, J.N. (2008 46th Annual Allerton Conference on Communication, Control, and Computing, 2008)
We investigate the fundamental secrecy limits of arbitrary wiretap channels using the information-spectrum approach and we provide a random coding theorem for the secrecy capacity under various secrecy metrics. We show how our result specializes to several recent results, e.g., compound channels, parallel channels, and fading channels. As a side benefit, our analysis shows that earlier results hold under more stringent secrecy metrics than previously established.